Optimization of ficus deltoidea using ultrasound-assisted extraction by box-behnken statistical design - Ong, Li Jing (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
In this study, the effect of extraction parameters (ethanol concentration, sonication time and solvent-to-sample ratio) on Ficus deltoidea leaves was investigated using ultrasound-assisted extraction by response surface methodology (RSM). Total phenolic content (TPC) of F. deltoidea extracts was identified using Folin-Ciocalteu method and expressed in gallic acid equivalent (GAE) per g. Box--Behnken statistical design (BBD) as the tool to find the optimal conditions for maximum TPC. Besides, the extraction yield was measured and stated in percentage. The optimized TPC attained was 455.78 mg GAE/g at 64% ethanol concentration, sonication time at 10 minutes and 20 mL/g of solvent-to-sample ratio whereas the greatest extraction yield was 33% with ethanol concentration of 70%, sonication time of 40 minutes and solvent-to-material ratio at 40 mL/g. The determination coefficient, R2 for TPC indicates that 99.5% capriciousness in the response could be clarified by the ANOVA model and there was 0.9681 of predicted R2 is in equitable agreement with the 0.9890 of adjusted R2. Present study exhibits that the ethanol-water as solvent, short time (10 minutes) and adequate solvent-to-sample ratio (20 mL/g) are the best condition for extraction.